Prevalence of sickle cell trait in dialysis patients - Luana Isaias; Suzane Bertoni; Ana Luiza Barbosa dos Santos; Esperança da Luz Tinoco Ribeiro; Lívia Borsato; Hye Chung Kang (Sociedade Brasileira de Patologia Clínica, 2013)
The sickle cell nephropathy is described as a homozygous sickle cell disease. However, there is no consensus as to the heterozygotes, thus other investigations are required to provide further information on this topic. This study aimed at determining the frequency of sickle cell trait in a population of chronic renal failure patients in the city of Niterói.